Transcervical Intrauterine Levobupivacaine or Lidocaine Infusion for Pain Control during Endometrial Biopsy - Nermin Kosus; Aydın Kosus; Ruveyda I Demircioglu; Serap A Simavli; Aysel Derbent; Esra Aktepe Keskin; Nilgun O Turhan (Pain Research and Management)
BACKGROUND: Endometrial biopsy is a common procedure for the investigation of many gynecological disorders including abnormal uterine bleeding, postmenopausal bleeding, abnormal cytology and infertility. Most women experience some degree of discomfort and pain during the procedure. Pain may occur during dilation of the cervix for insertion of the catheter and during endometrial biopsy, which further aggravates pain by inducing uterine contraction.